New principles for a new world - Waetjen, Thembisa (PINS-Psychology in Society, 2024)
Williams, Michelle & Satgar, Vishwas (eds) (2013) Marxisms in the 21st century: Crisis, critique and struggle. Johannesburg: Wits University Press. ISBN 978-1-86814-753-3 pbk. Pages vi + 298